The running grave [compact disc, unabridged] - Galbraith, Robert (Galbraith, Robert. Cormoran Strike novel., 2023)
Private detective Cormoran Strike is contacted by a worried father whose son joined a religious cult, where Strike finds sinister doings and unexplained deaths. Strike's business partner, Robin Ellacott, decides to infiltrate the cult, and she travels to Norfolk to live incognito among its members. But in doing so, she is unprepared for the dangers that await her there and for the toll it will take on her.